Diferentes proporções de fosfato bicálcico e fosfato de rocha em dieta de bovinos - Coneglian, Sabrina Marcantonio (2006)
The objectives of this work were to evaluate the effects of replacing dicalcium phosphate (DP) by rock phosphate of Araxa (RPA), in growing steer diets, over disappearance and apparent absorption of phosphorus (P), calcium (Ca) and fluoride (F), and partial and total nutrient apparent digestibility, ruminal parameters, microbial efficiency and plasma parameters. Were used five Holstein steers eighteen month old, weighting 280 kg, implanted with ruminal cannula. Statistical design was a 4x4 Latin square, were treatments consisted of 0, 25, 50, 75 and 100% replacement of DP by RPA on mineral supplement placed into the rumen through ruminal cannula. Replacement of DP by RPA showed a linear decrease (P<.05) in total disappearance and intestinal and total apparent absorption of P, a linear decrease (P<.05) in intake, duodenal flow, fecal flow and disappearance of F, and a linear decrease (P<.05) of ruminal, intestinal and total apparent absorption of F. Treatments did not affect (P>.05) disappearance of Ca and digestion of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), ether extract (EE), and non-fiber carbohydrates (NFC), and total digestible nutrients (TDN). Replacement of DP by RPA did not affect (P>.05) plasma P, nitrogen intake, microbial efficiency and ruminal bacteria composition. Treatments did not affect (P>.05) ruminal pH and ruminal NH3 concentration, but in all treatments these parameters showed a quadratic response to post feeding time. These results showed a possible use of RPA in growing steer diets in replacement of DP without affecting ruminal fermentation and digestion parameters, but P requirements should be considered because P apparent absorption is affected.